2015
DOI: 10.1021/acs.chemmater.5b01622
|View full text |Cite
|
Sign up to set email alerts
|

KEu(MoO4)2: Polymorphism, Structures, and Luminescent Properties

Abstract: In this paper, with the example of two different polymorphs of KEu(MoO 4 ) 2 , the influence of the ordering of the A-cations on the luminescent properties in scheelite related compounds (A′,A″) n [(B′,B″)O 4 ] m is investigated. The polymorphs were synthesized using a solid state method. The study confirmed the existence of only two polymorphic forms at annealing temperature range 923−1203 K and ambient pressure: a low temperature anorthic α-phase and a monoclinic high temperature β-phase with an incommensura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 48 publications
(97 reference statements)
0
29
0
Order By: Relevance
“…In most cases, a low doping of Eu 3+ activator leads to a weak luminescence, whereas heavy doping will lead to concentration quenching. For some fully concentrated Eu 3+ compounds, no concentration quenching occurs at all, for example, Eu 2 WO 6 (Qin et al, 2009), KEu(MoO 4 ) 2 (Morozov et al, 2015), K 5 Eu(P 2 O 7 ) 2 (Zhao et al, 2019a) and EuZnB 5 O 10 (Hao et al, 2014). These materials are very likely to suffer from high photon flux during their application.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, a low doping of Eu 3+ activator leads to a weak luminescence, whereas heavy doping will lead to concentration quenching. For some fully concentrated Eu 3+ compounds, no concentration quenching occurs at all, for example, Eu 2 WO 6 (Qin et al, 2009), KEu(MoO 4 ) 2 (Morozov et al, 2015), K 5 Eu(P 2 O 7 ) 2 (Zhao et al, 2019a) and EuZnB 5 O 10 (Hao et al, 2014). These materials are very likely to suffer from high photon flux during their application.…”
Section: Introductionmentioning
confidence: 99%
“…The succession of structural types with change in the ionic radii of R 3+ and M + , met in double molybdates and tungstates, has been described in a review paper of Klevtsov and Klevtsova [5] .The compounds can be listed in 22 structural types distributed into four basic classes taken as parent types: scheelite CaWO4, wolframite (Fe,Mn)WO4, γ-RbPr(MoO4)2 and glaserite-type (trigonal) KAl(MoO4)2. Recently the incommensurately modulated scheelite-like structure have been found in KNd(MoO4)2 [6] , KSm(MoO4)2 [7] and KEu(MoO4)2 [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Some of them represent a tetragonal structure, namely NaGd(MoO 4 ) 2 , with the space group I4 1 /a . When metals distribution is more complicated the symmetry of the framework lowers toward a monoclinic one or became a modulated one, like KEu(MoO 4 ) 2 and NaEu(MoO 4 ) 2 …”
Section: Introductionmentioning
confidence: 99%
“…A previous X‐ray single diffraction study has shown that the symmetry of the ARE(MoO 4 ) 2 compounds depends on the A/RE content, temperature and synthetic procedure . The A/RE substitution process is expected to be quite complex leading to incommensurately modulated structures .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation